Albert Ballin - Gerhardt, Johannes (Mäzene für Wissenschaft, 2009)
An unprecedented ascent: from the thirteenth child of a poor Jewish emigration agent to the "sovereign of seafaring" and "friend" of the emperor. No wonder that Albert Ballin was one of the most outstanding figures of the Wilhelmine Empire. From the very beginning, he caused a stir at the Hamburg-American Packetfahrt-Actien-Gesellschaft, or Hapag for short. Under the leadership of their manager Ballin, the latter became the world's largest shipping company. From 1907 until his tragic death on November 9,1918, Ballin was a member of the board of trustees of the Hamburgische Wissenschaftliche Stiftung and had a special impact here as well. This biography traces the extraordinary life of this man. [German edition]